ANALYSIS OF THE EFFECT OF OPEN UNEMPLOYMENT RATE, POVERTY, AVERAGE YEARS OF SCHOOLING, AND PER CAPITA GROSS DOMESTIC PRODUCT ON INDONESIA'S INCLUSIVE ECONOMIC DEVELOPMENT IN 2016-2021 - Aza Amalia; Lorentino Togar Laut; Emma Dwi Ratnasari (Transpublika Publisher, 2023)
Good economic development is not only measured by the growth rate but also considers various factors related to community welfare. In Indonesia, the current economic growth is insufficient to address social issues such as inequality, poverty, and limited access to employment opportunities for the population. This study aims to examine the impact of the Open Unemployment Rate, Poverty, Average Years of Schooling, and GRDP Per Capita on Indonesia's inclusive economic development between 2016 and 2021. The study utilizes secondary data from the Central Statistics Agency (BPS) and the National Development Planning Agency (Bappenas). Panel data regression analysis techniques, employing the Partial Adjustment Model (PAM) approach through the E-views 10 program, are applied to analyze the data. The findings reveal that the Open Unemployment Rate and poverty variables have a significant negative impact on Indonesia's inclusive economic development. Conversely, Average Years of Schooling and GRDP Per Capita have a positive and significant effect on Indonesia's inclusive economic development from 2016 to 2021.